2011
DOI: 10.1002/cmr.a.20219
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric materials in magnetic resonance

Abstract: High permittivity materials find extensive use in high frequency communications devices due to their small size (compared to lumped element circuits), low losses and physical robustness. Recently, these types of materials have been applied in high field magnetic resonance imaging, based upon earlier work in electron paramagnetic resonance. This review article describes the basic properties of high permittivity materials, how they can be formed into both discrete resonators and also into deformable water-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
154
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 67 publications
1
154
0
1
Order By: Relevance
“…However, UHF MRI of deep organs is complicated due to the use of relatively high frequency of the radiofrequency (RF) signal as well as the effect of much shorter signal wavelength in biological tissue. These factors can lead to destructive interference within the sample, causing field inhomogeneity and lower signal-to-noise (SNR) at deep locations of the body [1]. In addition, the RF power deposition is increased due to the use of a higher frequency, and specific absorption rate (SAR) levels become an important concern from a radiation exposure safety point of view [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, UHF MRI of deep organs is complicated due to the use of relatively high frequency of the radiofrequency (RF) signal as well as the effect of much shorter signal wavelength in biological tissue. These factors can lead to destructive interference within the sample, causing field inhomogeneity and lower signal-to-noise (SNR) at deep locations of the body [1]. In addition, the RF power deposition is increased due to the use of a higher frequency, and specific absorption rate (SAR) levels become an important concern from a radiation exposure safety point of view [2].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum dielectric constant of the two conformal pads with a thickness of 5 mm placed left and right of the pelvis model was found to be about 400; meanwhile, the partial body SAR, maximum mother 10 g local SAR and maximum fetus 10 g local SAR were 1.75, 7.19 and 2.45 W/kg, respectively. The optimum dielectric constant of the two conformal pads with a thickness of 5 mm placed anterior and posterior of the The contribution to the B 1 field and SAR from the conductivity of HDM was much less than that from the relative dielectric constant due to the low ratio of conduction to displacement current [25], however, the conductivity does vary with different relative dielectric constant in different HDM. To further explore the influence of the variances of conductivity of HDM on B 1 field and SAR, the simulation was implemented as follows: relative dielectric constant set as 515, conductivity varied from 0.1 to 0.6 S/m with a step of 0.1 S/m.…”
Section: Discussionmentioning
confidence: 96%
“…This is because of the enhancement of the B 1 field for a given input power in the regions that are surrounded by the HDM [16,25]. The B 1 field distribution of the coil is altered by the strong displacement currents caused by the existence of the HDM, resulting in stronger B 1 fields in the region of interest (ROI) [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…dielectric materials, between a radiofrequency (RF) coil and the sample in magnetic resonance (MR) imaging applications [1,2]. In-vivo studies have demonstrated these benefits, for example, in cardiac imaging [3] and cerebral imaging [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dielectric materials with a high relative permittivity (εr = 1,200) have been proposed to improve coil performance for MR applications at 3 T [5]. Various studies have demonstrated the benefits of integrating dielectric materials with commercially manufactured coils [1,2]. In at least one case, a complete annular dielectric sleeve was simulated surrounding an entire head-sized birdcage coil [6].…”
Section: Introductionmentioning
confidence: 99%